Strangers in homeland: A psychoanalytical analysis of violence against refugee - Alves, Vera Lucia da Silva; Santos, Wueslle Thibes dos (Seven Editora, 2023)
Refugee issues have often appeared in the news in recent years, mobilizing various debates around the globe. This is because the flow of immigration has increased exponentially over the past 10 years, with Syria, Afghanistan, and southern Sudan as its main countries. Despite this, many other countries produce new refugees every day. This happens for a variety of reasons, including internal conflict, sectarian wars, and famine. With this symptom that destabilizes a prior order of things, the opposition also appears. This gives rise to violent speeches against refugees, often regarding them as terrorists or invaders. The contribution of psychoanalysis to this question may come from several theoretical fields, but for this article, some concepts were selected to contribute to the development of the discussion. The refugee would be in the position of a familiar stranger, who invades a wall assembly that aims at security and to prevent what is out there (indetermination and malaise) from entering. Violence then appears in various ways, as something systemic and invisible and which serves to justly recover some kind of homeostasis from an undisturbed state before the war, or as symbolic violence, being referred to as what reduces the thing to a simple trace, and attributes external perspectives to itself, and then language itself is violence. For this analysis were used several authors of psychoanalysis, such as Sigmund Freud, Jacques Lacan, Slavoj Zizek, and Christian Dunker.  DOI:https://doi.org/10.56238/alookdevelopv1-116